THE CONCEPT OF STRATEGIC AGENDA APPLIED TO A STUDY OF THE FEDERAL SUPREME COURT OF BRAZIL - Albuquerque, Grazielle (Brazilian journalism research, 2024)
ABSTRACT – The article presents the concept of strategic agenda-setting with the objective to propose an analysis model which may help to analyse how the Judiciary communicates. By understanding that the Courts have no direct contact with society, the strategic agenda points out that the way in which the Judiciary shows itself in the public debate depends on communication dynamics. This means that there is an internal axis related to communication advisory and an external axis related to coverage. Such dynamics depend on constraints and opportunities of the political context. It is a policy that sets the tone for the Judiciary to communicate. The concept brings together approaches from communication theory (agenda-setting) with judicial behaviour (strategic model), using quantitative data and semi-structured interviews, and creates an analytical model that was applied to the Federal Supreme Court (STF) of Brazil between the years 1988 to 2004. RESUMO – O artigo apresenta o conceito de agendamento estratégico para propor um modelo de análise da comunicação do Judiciário. Considerando a ausência de contato direto dos Tribunais com a sociedade, destaca-se que a forma como o Judiciário se posiciona no debate público depende da dinâmica comunicacional. Isso implica em um eixo interno, relacionado à assessoria de comunicação, e um eixo externo, ligado à cobertura. Tais dinâmicas são influenciadas por constrangimentos e oportunidades do contexto político. Assim, a política estabelece o tom da comunicação judicial. O conceito combina abordagens da teoria da comunicação (definição de agenda) e comportamento judicial (modelo estratégico), utilizando dados quantitativos e entrevistas semi-estruturadas. O modelo analítico foi aplicado ao Supremo Tribunal Federal (STF) brasileiro entre 1988 e 2004. RESUMEN – El artículo presenta el concepto de agenda estratégica para proponer un modelo de análisis de la comunicación del Poder Judicial. Se destaca que la forma en que el Poder Judicial se posiciona en el debate público depende de la dinámica comunicacional, con un eje interno relacionado con la asesoría de comunicación y otro externo vinculado a la cobertura. Estas dinámicas están influenciadas por las restricciones y oportunidades del contexto político, estableciendo así el tono de la comunicación judicial. El concepto combina enfoques de la teoría de la comunicación y el comportamiento judicial, utilizando datos cuantitativos y entrevistas semiestructuradas. El modelo analítico se aplicó al Supremo Tribunal Federal (STF) brasileño entre 1988 y 2004.